Establishing expert consensus on Chinese herbal medicine for rheumatoid arthritis management in Singapore - Ang Loh; Huijuan Li; Wai Ching Lam; Yan Yin Tjioe; Warren Fong; Linda L.D. Zhong (Journal of Traditional Chinese Medical Sciences, 2025)
Objective: To establish consensus on Chinese Herbal Medicine (CHM) for rheumatoid arthritis (RA) among 21 Singaporean experts, this study addressed the lack of CHM clinical practice guidelines (CPGs) in Singapore. Despite advancements in RA therapies, the disease's progressive nature and high costs of novel treatments worsen disparities in management and outcomes. The initiative aimed to bridge this gap by developing expert-backed recommendations for CHM use in RA care. Methods: The group of experts conducted two rounds of Delphi surveys containing 29 items identified from a literature review. Consensus was defined as ≥75% of votes in dichotomized ratings on a five-point ordinal scale for recognition. Items that did not reach consensus were discussed in a focus group with four selected experts. Results: Nineteen experts completed both rounds of Delphi surveys. A consensus was reached for 27 items, which encompassed Chinese medicine rationale, pattern differentiation, management, CHM prescription, and co-effectiveness with pharmacological therapy. Collective expert opinions were formed for the two remaining items. All items received a recognition score >3.5. Conclusions: The consensus derived from this study provides a foundation for CHM CPGs for RA in Singapore. However, the findings are limited by the demographic composition of the experts and the representativeness of the patient pool.